2017
DOI: 10.3389/fmicb.2017.00017
|View full text |Cite
|
Sign up to set email alerts
|

Key Impact of an Uncommon Plasmid on Bacillus amyloliquefaciens subsp. plantarum S499 Developmental Traits and Lipopeptide Production

Abstract: The rhizobacterium Bacillus amyloliquefaciens subsp. plantarum S499 (S499) is particularly efficient in terms of the production of cyclic lipopeptides, which are responsible for the high level of plant disease protection provided by this strain. Sequencing of the S499 genome has highlighted genetic differences and similarities with the closely related rhizobacterium B. amyloliquefaciens subsp. plantarum FZB42 (FZB42). More specifically, a rare 8008 bp plasmid (pS499) harboring a rap-phr cassette constitutes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 81 publications
0
15
0
1
Order By: Relevance
“…Genome sequencing and analysis of B. amyloliquefaciens ZJU1 revealed that it encodes an impressive arsenal of antimicrobial compounds, among which four products exhibiting highly antifungal activity were detected in situ (Loeffler et al, 1986;Chen et al, 2009;Um et al, 2013;Li et al, 2014;. In particular, non-ribosomally synthesized lipopeptides and polyketides have been demonstrated to make a significant contribution to plant disease protection (Molinatto et al, 2017). In addition, ZJU1 can produce a variety of bioactive VOCs to antagonize phytopathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequencing and analysis of B. amyloliquefaciens ZJU1 revealed that it encodes an impressive arsenal of antimicrobial compounds, among which four products exhibiting highly antifungal activity were detected in situ (Loeffler et al, 1986;Chen et al, 2009;Um et al, 2013;Li et al, 2014;. In particular, non-ribosomally synthesized lipopeptides and polyketides have been demonstrated to make a significant contribution to plant disease protection (Molinatto et al, 2017). In addition, ZJU1 can produce a variety of bioactive VOCs to antagonize phytopathogens.…”
Section: Discussionmentioning
confidence: 99%
“…B. amyloliquefaciens subsp. plantarum S499 harbors an 8‐kb plasmid absent from strain FZB42, as well as genes encoding putative regulatory and transport proteins that may help to explain why the two strains differ in CLP production as well as in how they perceive and respond to environmental cues . The plasmid‐cured derivative of S499 produced increased quantities of surfactins and fengycins, but fewer iturins than did the wild type.…”
Section: Bacillus: Classical Biocontrol Agentsand a Focus On Cyclic Lmentioning
confidence: 99%
“…CLP concentrations in both strains were increased in the presence of the pathogens Cladosporium cucuminerum and Fusarium oxysporum f.sp. radicis‐lycopersici , implicating the activity of regulatory signal molecules produced by the fungi . However, it also has been proposed that concentrations of CLPs produced in situ by strains like FZB42 are insufficient to mediate direct pathogen inhibition and instead, that the main mechanism responsible for biocontrol activity is ISR.…”
Section: Bacillus: Classical Biocontrol Agentsand a Focus On Cyclic Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Серед антагоністів фітопатогенних мікроорганізмів слід відмітити представників роду Bacillus, які продукують різні антимікробні речовини, такі як циклічні ліпопептиди, а також літичні ферменти та хітинази (Alvarez et. al., 2012;Ji et al, 2013;Meena & Kanwar, 2015;Yamamoto et al, 2015;Bodhankar et al, 2017;Dimkić et al, 2017;Molinatto et al, 2017;Rishad et al, 2017). Ліпопептиди, які продукуються B. subtilis, B. amyloliquefaciens, B. pumilus (мікосубтилін, фенгіцини А і В, ітурин), проявляють антифунгальну дію, тоді як сурфактин має широкий спектр антибактеріальної дії (Ji et al, 2013;Khong et al, 2013;Meena & Kanwar, 2015).…”
Section: вступunclassified